Analisis User Experience Terhadap Kepuasan Pengguna Menggunakan Heart Framework Pada Aplikasi Grab - Muhammad Noer; Ilham Ramadhani; Muhammad Ilyasa Mahardhika; Anita Wulansari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Grab is an online transportation service provider using an application. This study aims to analyze user experience on user satisfaction in the grab application. By using heart metrics as a research method, 5 indicators are used as benchmarks for calculations such as Happiness, Engagement, Adoption, Retention, and Task Success and utilize the level of usability. With a mixed average value of 0.83 which indicates that the usability level has reached a very high level.